Challenges Faced by Vocational Teachers in Public Skills Training Institutions: A Reality in Malaysia - Ismail, Khuzainey; Mohd Nopiah, Zulkifli; Rasul, & Mohamad Sattar (Journal of Technical Education and Training, 2018)
Teachers in Technical and Vocational Education and Training (TVET) play a pivotal role in ensuring skilled graduates with excellent personality. However, some TVET teachers in developing world face challenges in fulfilling this role. Thus, this study explored the challenges that are faced by vocational teachers (who are assigned to teach skills courses) from public skills training institutions in Malaysia. Using qualitative research design, this study conducted semi-structured interviews on 13 purposively selected participants from the Department of Skills Development and personnel under the Ministry of Human Resources and Ministry of Youth and Sports, which included six management staff and seven vocational teachers. Following the analysis using nVIVO, this study identified six core challenges faced by  vocational teachers: (1) disinterest and lack of motivation in teaching the assigned skills subjects; (2) lack of skills qualifications and industrial experiences (which are necessary as vocational teachers; (3) meeting the needs of students with low academic grades which require  extra teaching effort with high emotional intelligence; (4) difficulty in attending professional courses due to limited budget allocation, rotation system, and heavy workload; (5) difficulty in article writing task; and (6) difficulty in using English as the medium of instruction. These findings demonstrate the strong need to address the challenges faced by these vocational teachers, particularly for the teaching of programmes based on the National Occupational Skills Standard (NOSS), in the public skills training institutions  to enhance the teaching and learning process in TVET.